The Impact of New Accounting Rules on the Operating Lease Contract (Damascus University Journal for legal sciences, 2025)
Today, interest in financial or operational leasing contracts has reached a new level of interest in the legislation of developed countries, as the Financial Accounting Standards Board issued an amendment under a new rule that has entered into force since the end of 2018, and according to this rule, public and private companies must recognize all lease contracts in their budgets. Provided that the duration of these contracts exceeds twelve months. This rule includes the operating lease. Prior to the amendment, operating leases were accounted for as off-balance sheet financing, meaning that the leased assets and liabilities associated with future operating lease payments were not included on the company's balance sheet. This previously allowed billions of dollars to be kept in American companies because they did not report their assets and liabilities on the general balance sheet. While we find that the Syrian legislator still does not fully observe the contract in its civil or commercial legislation, despite the economic and industrial power it has become in developed countries.
Keywords: Operating Lease Contract; Lease Contract; Lessee Contract; Lessor